West German foreign aid, 1956-1966 : its economic and political aspects - Holbik, Karel; Myers, Henry Allen (Boston : Boston University Press, 1968)
The purpose of this book is to show an analysis of the economic and political implications of the West German aid. and its contributions to Foreign Aid. The authors give a short review of the performance of the West German economy, especially the export performance, during the period considered.
Includes index
Bibliography: p. 140-153.
usc 30/10/18
Loans
Keywords: Economic assistance, German